The 57 kb deletion in cystinosis patients extends into TRPV1 causing dysregulation of transcription in peripheral blood mononuclear cells - Freed, K.; Blangero, J.; Howard, T.; Johnson, M.; Curran, J.; Garcia, Y.; Lan, H.; Abboud, H.; Moses, Eric (2011)
Background: Cystinosis is an autosomal recessive disease characterised by the abnormal accumulation of lysosomal cystine. Mutations in the cystinosin gene (CTNS) represent known causes for the disease. The major cystinosis mutation is a 57 kb deletion on human chromosome 17p13 that removes the majority of CTNS and the entire adjacent gene, CARKL/SHPK. Objectives: In order to identify other genes that may influence the cystinosis pathobiological pathway, peripheral blood mononuclear cells (PBMC) were collected from cystinosis family members, and DNA and RNA extracted. Results: Using whole genome transcriptional profiling, transient receptor potential vanilloid 1 (TRPV1) was found to be differentially expressed in association with cystinosis. This was verified using TaqMan qRT-PCR. There was a 72% reduction in PBMC TRPV1 mRNA levels in cystinosis individuals homozygous for the 57 kb deletion (n=6) compared to unaffected individuals without the deletion (n=6) (p=0.002). TRPV1 is a sensory receptor located on chromosome 17p13, adjacent to CARKL/SHPK. It was ascertained that the 57 kb deletion extends from exon 10 of CTNS, upstream through CARKL/SHPK, to intron 2 of TRPV1, thus deleting the first two non-coding exons. Conclusion: This is the first study to report that the 57 kb deletion extends into the TRPV1 gene causing dysregulation of transcription in PBMC isolated from cystinosis patients.